Inhibition of feline leukemia virus replication in chronically infected cell line utilizing RNA interference - Ornelas, Sócrates Souza (2012)
Feline Leukemia virus (FeLV) is a pathogenic retrovirus endemic among domestic cats, remaining a serious disease since its discovery in 1964. RNA interference (RNAi) is a process in which double-stranded RNA induces the post-transcriptional sequence-specific degradation of homologous messenger RNA. At present, RNAi technology is regarded as a potential strategy for the treatment of various diseases as it can be used to inhibit the expression of desired peptides/proteins. This study aimed to apply RNAi technology to inhibit the replication of FeLV. We examined the effect of vector-mediated transfer and expression of FeLV specific short hairpin RNA (shRNA) against p27 protein expression and replication of FeLV in a feline T-cell line chronically infected with FeLV (3201-EECC). Three shRNA homologous to the FeLV gag gene were synthesized, cloned and transfected into a feline fibroblastic cell line (CrFK) expressing FeLV which efficiently reduced FeLV p27 protein expression, consequently decreasing and inhibiting the viral replication in a chronically FeLV infected feline T-cell line (3201-EECC). The expression of shRNA against FeLV gag gene showed markedly lower p27 levels and viral replication in both cell lines, 3201-EECC and CrFK. These results provide useful information to pave the road for the development of a gene therapy strategy to control FeLV and related pathogenic retrovirus infections in the future.